Local community perceptions of sea turtle egg use in Tortuguero, Costa Rica. (15th February 2021) - Mejías-Balsalobre, Carmen; Restrepo, Jaime; Borges, Gilberto; García, Raúl; Rojas-Cañizales, Daniela; Barrios-Garrido, Héctor; Valverde, Roldán A.
Abstract: Tortuguero is a small Caribbean village of Costa Rica, where sea turtles have always played a central role in the culture and economy. Historically, Tortuguero based its economy on the exploitation of natural resources, including marine turtles. However, thanks to long term conservation efforts, policy modifications and a change in the mindset of the community, this village is now globally recognized as an example of how marine turtles can be used to generate significant revenue in a non-extractive way, through ecotourism. Nevertheless, poaching of nests and egg trade still occurs in the area. This study identifies the perceptions and attitudes of the local community towards the consumption and trade of sea turtle eggs and its impact on conservation. From October to December 2017, a total of 187 questionnaires were distributed to the community of Tortuguero, and 17 semi-structured interviews were conducted with local key informants. Our results show that sea turtle egg consumption still persists within the community, and it is perceived as a frequent practice (Questionnaire Respondents (QR); 62.2%, n = 51/Interview Respondents (IR); 58.8%, n = 10). There is awareness among villagers about the negative effects of sea turtle egg consumption mainly on the economy (QR; 76.7%, n = 89), tourism (QR; 88.4%, n = 107) and conservation (QR; 87%, n = 107), and the practice is negatively regarded (QR; 77%, n = 107/IR; 76.5%, n = 13). Nevertheless, consumption continues as a traditional practice (QR; 26.7%, n = 28/IR; 41.2%, n = 7), facilitated by the ease to obtain eggs (QR; 19.4%, n = 20/IR; 76.5 n = 13) and the persisting belief of their aphrodisiac properties (QR 18.6%; n = 19/IR 23.5%; n = 4). Despite this and the perceived lack of enforcement, interviewees stated that most consumers do not risk taking the eggs and they buy them from local poachers (IR; 88.2%, n = 15), who are usually associated with substance abuse problems. In addition, most interviewees (94.1%, n = 16) affirmed that consumption in the community has decreased over the last 10 years, and that the majority of eggs extracted from Tortuguero are traded with nearby Caribbean communities (76.5%, n = 13). The destination of the eggs seems to depend on the area from which they were taken and prices range widely depending on the seller and the trade area. Overall, this study provides an improved understanding of the local perception of egg consumption and trade dynamics. Additionally, it provides insights into the challenges of tackling this issue in Costa Rica's Caribbean coast. We hope that our conclusions will contribute to the improvement of current conservation and management strategies in the region. Highlights: Sea turtle egg use is perceived as a frequent practice within the community of Tortuguero, though it is negatively regarded. There is more awareness of the negative effects of sea turtle egg use on the economy and conservation than on the human health. Consumption continues as a traditional practice, but it is perceived to have decreased over the last 10 years. Most consumers do not risk taking the eggs and buy them from local poachers, who are associated with substance abuse. The majority of eggs extracted from Tortuguero are traded with nearby Costa Rican Caribbean communities.